Online Yellow Pages for older adults: a usability study - Aharon, Shai (Auckland University of Technology, 2007)
This research examines the usability of online Yellow Pages for older adults. Older adults are an increasingly important group of internet users but they have not had much web design attention, even though previous studies indicate that they face various difficulties when using the internet. This study primarily uses usability testing to examine the actual experience of older adults when using the online Yellow Pages. The findings from this study indicated that the online Yellow Pages has some design deficiencies in relation to older users, namely; small clickable icons, not easily recognised clickable items, important information located at the screen periphery, non-standard design of pages, missing headings for some clickable areas, poor distinction between content and advertisements, a poor search mechanism, and no spellchecker. However, positive aspects were also discovered, including; a good colour schema, appropriate use of hierarchical menus, simple language, a map facility, and national search. The study showed that the Yellow Pages book is a highly valued product for the senior age group. There was strong motivation to use it because the information acquired related to important parts of their lives. In addition, the book assisted them to make appropriate use of this information. The study found that the online Yellow Pages was also regarded as a valuable product because it was seen to provide some of the functionality of the book. In addition, the online version was perceived to have additional value in that it provided national searching and location maps. However, computer and internet familiarity had a strong influence on prospective take up. Whether the user had the habit of having the computer on and immediately available also had a strong influence on users’ expectation that they will become regular users of the online Yellow Pages. This study contributes the first usability research done for the Yellow Pages web site among older adults. It builds on the existing understanding of older users’ needs when using the Internet, and will benefit web designers and hopefully, in turn, older users.